Does a pay-for-performance health service model improve overall and rural–urban inequity in vaccination rates? A difference-in-differences analysis from the Gambia. (December 2022) - Sowe, Alieu; Namatovu, Fredinah; Cham, Bai; Gustafsson, Per E.
Highlights: Vaccination coverage increased by 16 percentage points in The Gambia during the period 2013–2020. Interestingly, non-intervention regions experienced slightly (12%) higher increments in coverage than the pay-for-performance intervention regions. Rural-favoured vaccination inequalities decreased more in the pay-for-performance group in comparison with the control group. Abstract: Objective: To assess whether the implementation of a results-based financing (RBF) project in The Gambia resulted in (1) improved national vaccination coverage (2) higher coverage in intervention than non-intervention areas, and (3) improvement in rural–urban coverage inequality. Methods: The study used a difference-in-differences design, based on repeated cross-sectional data from The Gambian Demographic and Health Surveys 2013 (N = 1650) and 2020 (N = 1456). Full vaccination (receipt of one BCG, 3 OPV, 3 DTP, and 1 measles-containing vaccine doses) and rural–urban vaccination inequality were our outcome variables. The intervention, RBF, was implemented in 5 of the 7 health regions. Covariates controlled for included child's sex, child's birth order number, socioeconomic status, ethnicity, distance from health facility, maternal education, mother's age group, mother's marital status, and mother's work status. Poisson regression with robust variance was used to estimate whether coverage changed, and difference-in-differences and difference-in-differences-in-differences were used to 'assess differences in vaccination coverage change and change in inequalities, respectively. Results: Total crude full vaccination coverage in The Gambia was 76% in 2013 and 84.6% in 2020. Overall vaccination significantly increased by 16% (95% CI: 9% to 24%) in 2020 compared to 2013, but with a smaller increase in intervention relative to non-intervention areas [PRR 0.88 (CI: 0.78–0.99)]. Rural-urban inequality in vaccination coverage decreased more – by 13% [0.87 (0.78–0.98)] – in RBF than non-RBF regions. Conclusion: Vaccination coverage improved over the study period though we have no evidence to ascribe the coverage gains to the RBF intervention. However, our study suggests that the RBF project has contributed to reducing rural–urban inequalities in the regions it was implemented.